1964
DOI: 10.1515/znb-1964-0806
|View full text |Cite
|
Sign up to set email alerts
|

Cesium Behaviour and Distribution in Man following a Single Dose of 137Cs

Abstract: The excretion and distribution of 137Cs in a 60 year old male given a single dose of 8,2 μC through a gastrostomy have been studied. The excretion rates and the concentrations in faeces, urine and blood are presented, as well as the distribution of 137Cs in several of the internal organs removed after death. The biological half-life for cesium in this study is approximately 100 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1966
1966
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This seems doubtful, in view of measurements of radiocaesium in humans as well as animals. For example, Madshus and Stromme (1964) found that the concentration of 13'Cs in the lumbar vertebrae of a human subject at 84 days after administration was one half to one fourth of the concentration in heart, spleen, kidney, lung and liver, and one seventh the concentration in gluteal muscle. Comparable results were obtained for human femur and soft tissues by Kaul et a1 (1966) after chronic exposure to environmental 13'Cs.…”
Section: Potassium Rubidium and Caesium In The Skeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems doubtful, in view of measurements of radiocaesium in humans as well as animals. For example, Madshus and Stromme (1964) found that the concentration of 13'Cs in the lumbar vertebrae of a human subject at 84 days after administration was one half to one fourth of the concentration in heart, spleen, kidney, lung and liver, and one seventh the concentration in gluteal muscle. Comparable results were obtained for human femur and soft tissues by Kaul et a1 (1966) after chronic exposure to environmental 13'Cs.…”
Section: Potassium Rubidium and Caesium In The Skeletonmentioning
confidence: 99%
“…There are some tissues listed in Publication 23 for which we found no published concentrations for humans for some or all of the elements K, Rb or C S . Estimates for these tissues were made in various ways: concentrations in blood vessels were assumed to be the same as in the aorta; the CS concentration in tongue was based on relative concentrations of 13'Cs (Madshus and Stromme 1964); the mass of K in the gastrointestinal ( G I ) contents was estimated by considering the total flow of material as well as the flow of K through the GI tract (Leggett and Williams 1986); the K concentration of separable connective tissue was based on the measured concentration of K in dog tendon (Manery 1954); and the CS concentration of adipose tissue was based on relative radiocaesium concentrations in adipose tissue and muscle of dogs (Furchner et al 1964).…”
Section: E C B H : E E Gmentioning
confidence: 99%